The Impact of Free Nutritious Meal Programs on Food Security: A Systematic Review - Yusriadi, Yusriadi (Journal of Indonesian Scholars for Social Research, 2025)
Food security is a persistent global challenge, particularly in low-income communities where access to nutritious food is limited. Free nutritious meal programs have been introduced to enhance food access and improve nutritional intake, especially for vulnerable populations such as children and low-income families. Despite their implementation, their overall impact on food security at the household and community levels remains underexplored. This systematic review examines the role of free nutritious meal programs in improving food security by evaluating their effects on food availability, accessibility, utilization, and stability. The study also highlights economic, social, and policy-related challenges affecting program sustainability. A systematic literature review was conducted following PRISMA guidelines. Data were sourced from academic databases such as Scopus, Web of Science, and PubMed, focusing on studies published in the last decade. Thematic analysis was employed to identify trends related to program effectiveness, policy integration, and long-term sustainability. Findings indicate that free meal programs enhance food security by increasing access to nutritious food, reducing malnutrition, and improving educational and economic outcomes. However, challenges such as financial constraints, logistical barriers, and policy fragmentation limit long-term success. While free nutritious meal programs offer short-term relief for food insecurity, their sustainability depends on strong policy support, financial investment, and integration with local food systems. Further research should explore scalable models to ensure their long-term effectiveness in diverse socio-economic settings.